A STUDY OF ANTIBACTERIAL UTILIZATION PATTERN IN A TERTIARY CARE HOSPITAL - JAHNAVI SIMHADRI; KOMAL KULKARNI; ASISH SV; SAPNA K DONGRE; NEETHU S GEORGE; DEVIPRASAD HEGDE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The objective of the study was to analyze the utilization pattern of antibacterials in a tertiary care hospital. Methods: A cross-sectional, prospective, observational study was conducted on patients admitted in inpatient departments of a tertiary care hospital for 6 months. Results: In the study, 152 prescriptions being assessed contained 17.2% antibacterials. The most commonly prescribed drug class among antibacterials was β-lactams (50%). Ceftriaxone and amikacin (10.58%) were the highly prescribed antimicrobials. Maximum number of antibacterials were prescribed as monotherapy and given as parenteral dosage forms. Among the fixed-dose drug combinations, the most commonly used combination was Cefoperazone + Sulbactam (10.58%). Conclusion: This study highlighted an overall pattern of antibiotic prescription in a tertiary care hospital. The most common infection for which the antimicrobials were prescribed was lower respiratory tract infection. Physicians preferred initiating prophylactic treatment than waiting for culture sensitivity test results. The most common antimicrobials prescribed were ceftriaxone and amikacin. Maximum number of prescriptions contained only one antimicrobial which is a favorable observation. Majority of prescriptions contained brand name which needs to be changed by an intervention.